2016
DOI: 10.20522/apjbr.2016.1.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Halal Certification: A Viewpoint From Malaysian Restaurant Managers

Abstract: This study focuses on halal certification from the viewpoint of Malaysian restaurant managers. The increasing demand of halal food from the Muslim and non-Muslim consumers has given a good indicator to the hospitality industry to have the eating establishments halal certified. A sample of 643 restaurant managers has been selected throughout Malaysia using systematic sampling. Questionnaires were distributed using mail survey and data was then entered to SPSS version 21 for further analysis. It is gathered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This condition will undoubtedly benefit producers who have halal-certified products. From the producer’s perspective, various studies have also highlighted the importance of halal certificates, such as: to build a better market position (Marzuki et al , 2012; Marzuki, 2016); as a marketing strategy that brings product differences from its competitors (Rajagopal et al , 2011); Halal-certified food has provided significant results in increasing sales, performance and growth in Singapore (Henderson, 2016; Yusuf et al , 2017; Yusuf et al , 2016). Therefore, Shafie and Othman (2006) stated that producers force the most excellent attempt to have a halal certificate because halal products construct a promising market.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This condition will undoubtedly benefit producers who have halal-certified products. From the producer’s perspective, various studies have also highlighted the importance of halal certificates, such as: to build a better market position (Marzuki et al , 2012; Marzuki, 2016); as a marketing strategy that brings product differences from its competitors (Rajagopal et al , 2011); Halal-certified food has provided significant results in increasing sales, performance and growth in Singapore (Henderson, 2016; Yusuf et al , 2017; Yusuf et al , 2016). Therefore, Shafie and Othman (2006) stated that producers force the most excellent attempt to have a halal certificate because halal products construct a promising market.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Taking an example of Malaysia, JAKIM established the halal logo and implemented the thorough halal certification system (Badruldin et al , 2012; Yusuf et al , 2016; Marzuki, 2016; Kamassi et al , 2020). Since the year 2005, JAKIM has produced the Manual Procedure for Malaysia Halal Certification (MPPHM), a reference document for Halal Certification which is concurrently used together with the Malaysia Halal Standard (Jabatan Kemajuan Islam Malaysia, 2015).…”
Section: Related Studiesmentioning
confidence: 99%
“…Henderson (2016) assert that the provision of halal food is considered as a critical competitive advantage for destinations who wish to brand themselves as Muslim-friendly. As a response to this, many food operators have realised the importance of having a halal certification to establish a better market position (Marzuki et al , 2012; Marzuki, 2016). Rajagopal et al (2011) suggested that halal certification can be considered as a marketing strategy that allows business entities to differentiate their products and services against their competitors.…”
Section: Introductionmentioning
confidence: 99%
“…Halal certification is a must for the food industry in Malaysia. (Marzuki, 2016). Consumers not only want health, safety and food quality.…”
Section: Literature Review Religionmentioning
confidence: 99%